Effects of transcranial direct current stimulation on balance after ischemic stroke (SANDE trial): Study protocol for a multicentric randomized controlled trial - Chagas, Tatiane de Jesus; Cravo, Igor Sandoval dos Santos; Bazan, Rodrigo [UNESP]; de Souza, Luciane Aparecida Pascucci Sande; Luvizutto, Gustavo José (Elsevier, 2021)
Background: Among the tools used for motor rehabilitation after stroke, transcranial direct current electrical stimulation (tDCS) aims to modify cortical excitability and improve motor function. Despite promising results, the effects of tDCS on balance after stroke have not yet been assessed using specific protocols. Therefore, this study will aim to evaluate the effects of tDCS and rehabilitation on balance after stroke. Methods: Eighty-two ischemic stroke patients across two inpatient rehabilitation sites in Brazil will be randomized into one of two treatment programs (anodic tDCS and sham tDCS), both associated with balance training, each 2 days/week, for six weeks and monitored for exertion, repetition and quality of movements. The primary outcome measure is the balance. Secondary outcomes will include clinical and functional measures. Outcome data will be assessed at two time points. Discussion: This trial will contribute to clarify if anodal tDCS is effective when associated with balance training to stroke recovery.
Keywords: Balance; Physiotherapy; Rehabilitation; Stroke; Transcranial direct current stimulation